Financial health of the Malaysian public universities: whither the way forward? - Mohd Said, Julia; Mamat, Suaniza; Nik Ahmad, Nik Nazli; Borhan, Amalina (Taylor & Francis, 2023)
The purpose of the paper is to examine the financial health of selected public universities in Malaysia. The study assessed the performance of Malaysian research universities, on the primary reserve ratio, viability ratio, return on net asset ratio and net operating revenue ratio, as well as the Hirschman-Herfindahl Index for revenue diversification from 2010 to 2020. Results suggest poor financial health, high dependence on government funding and revenue volatility. Several universities recorded consecutive financial deficits in recent years. Third-stream revenues are low, and the universities are struggling to generate the 25% self-generated revenue target set by the government. This paper provides longitudinal empirical data on the financial health of public universities and has important implications for policymakers and university management in budget allocation and financial management decisions, particularly given the adverse financial impacts of the COVID-19 pandemic.